Skunked! : Calpurnia Tate, girl vet - Kelly, Jacqueline (Kelly, Jacqueline. Calpurnia Tate, girl vet., 2016)
"When Travis discovers an abandoned baby skunk, he can't help but bring it home and take care of it. Stinky, as Travis names him, settles in pretty well. But when Travis discovers Stinky's litter-mate, Winky, who is in need of some help, things get complicated around the Tate house"--